Government Policy Solution to Build up Social Welfare by Decentralization: An Overview - Mansyur Achmad; Ratna Wati; Wahyu Tri Putranto (Jurnal Mantik, 2022)
The decentralization scheme has become a familiar issue around the world for the last 2 decades. Gaps between the degree of decentralization around the world seem true, but still have no agreement towards the question relating to which country is more decentralized? Because of the difference between meaning and sizing in various research. Actually, a proper evaluation to determine the degree of decentralization in a country could undertake on the condition that an inclusive method is acquired instead of simplifying its complex characteristic into solitary measure of autonomy. The interrelation between those various measures of decentralization is considerable. Thus, it should be noticed that there is none of one-size-fits-all index of the degree of decentralization in a country. Because there's a wide variety of research towards it, though there is also literature on decentralization outcomes. The results have been mixed not only because decentralization can take many shapes and mix in different countries, moreover it is due to the various tool which might unusual results under diverse conditions. Thus, reaching a precise definition of decentralization and linking it to specific research is neither possible nor desirable because the simple premise generalizes everything and produces pitfalls that can be vague instead of clarify those facts. What else more significant than the need of an actual contexts but in appropriate methods which go beyond the truth by deed such as spending decentralization and considering the political and institutional background for particular issues on trial.